Some new Brunn-Minkowski-type inequalities in convex bodies - Zhao Chang-Jian; Leng Gangsong; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
We establish some analogues of the Brunn-Minkowski inequalities on convex bodies and the Minkowski inequality and their inverse versions. As an application, we generalize and improve some interrelated results.